A Case Study Of Forms And Symptoms Of Culture Shocks Of The Foreign Students In Yogyakarta - Pradita, Intan (Journal of English and Education (JEE), 2013)
Entering multicultural society involves two participants, foreigners and natives. Due to globalization issues, multicultural society are required to have not only a good language competence but also a deep understanding of culture and religious belief. A long process of understading each other force the praticipants to have a good adaptation, which reveals some problems, such as culture shocks and alienation. Moreover, these problems hang on both parties. Therefore, analyzing the symptoms and forms of culture shocks is interesting leading to the way to overcome. One sample of multicultural society grows in Yogyakarta. The number of foreigners aim to study Bahasa Indonesia deal with Yogyakarta people as native Javanese are unique for their inquiries and comments towards Javanese culture. This research shows that although some forms of culture shocks strongly happened, they finally could manage to adapt with some strict normative rules and make friends to Indonesian people.Keywords: intercultural communication, cultural shocks